Kronologi Penemuan Mayat Wanita Korban Mutilasi Dalam Koper di Ngawi - Hutapea, Rinsan Maratur; Yusuf, Hudi (Media Hukum Indonesia (MHI), 2025)
The case of the discovery of a mutilated female body in a suitcase in Ngawi has attracted public attention due to the elements of violence and horrific crime. The victim's body was found on January 23, 2025 in a ditch in Dadapan Village, Ngawi. The victim's identity was revealed as Uswatun Khasanah (29), whose body was found without a head and legs. The investigation led to the main suspect, Rohmad Tri Hartanto alias Antok (32), who had a close relationship with the victim. The motive for the crime is suspected to be related to jealousy and personal problems. The victim's body parts were found in several separate locations, indicating a planned action by the perpetrator. This case highlights the urgency of preventing violence in personal relationships and the importance of strict law enforcement against mutilation crimes.